Respiratory Pathogens in Bronchoalveolar Lavage in a Puerto Rican Population Infected with the Human Immunodeficiency Virus - De Jesús-Berríos, Yohana; González, Sheila; Santé, María (Puerto Rico Health Sciences Journal, 2005)
Objective. To describe the respiratory pathogens found in the bronchoalveolar lavage of a Puerto Rican population infected with the human immunodeficiency virus (HIV). Background. Empirical treatment is an accepted strategy for management of HIV-related pneumonia, but it is usually recommended for countries that have knowledge of the prevalent organisms in their population. In Puerto Rico, we have relied on data from the United States, but ethnic and geographical differences have been reported. Design. Case series of a HIV-infected population admitted to an academic hospital in Puerto Rico because of respiratory symptoms and who underwent diagnostic standard bronchoalveolar lavage. Results. From August 1998 to March 2000, 32 bronchoalveolar lavages (BAL) were performed in 31 Puerto Rican HIV patients. Nine (31%) were female. Mean age was 37 years old. Predominant mode of infection of the virus was intravenous drug use in men and heterosexual contact in women. BAL was diagnostic in 17/32 (53%) of the cases. Identified respiratory pathogens were Pneumocystis carinii (5), Mycobacterium tuberculosis (4), Staphylococcus aureus (2), Pseudomonas aeuruginosa (1), Bordetella bronchiseptica (1), viridans streptococcus (1), Histoplasma capsulatum (1), Cytomegalovirus (1), and, Mycobacterium kansassi (1). Retrospective review of medical records of non bronchoscoped patients for the period added six culture confirmed tuberculosis cases increasing tuberculosis rate to 18% (10/56). Conclusions. Tuberculosis appears to be a more frequent pathogen in Puerto Rico than is reported in the United States. A larger study is needed to confirm this finding and thus to clarify whether an initial presumption of tuberculosis should be assumed in the Puerto Rican HIV population.